Propuesta de intervención en clínica psicoanalítica y psicología educativa en el establecimiento penitenciario de mediana seguridad y carcelario de Pereira. (2013)
This work has as main objective to present the final report of academic practice performed in the Establecimiento Penitenciario de Mediana Seguridad y Carcelario de Pereira a diagnosis is made intervention from the needs of the organization, therein lies the need to provide a space psychotherapeutic assessments support in security phase change, the formation of different workshops and psycho-educational brigades, all aimed at the population of jail inmates; from there, that the lines of action proposed for this report are supported in the clinical axis from Lacan´s psychoanalysis and the psychoeducational.